An introduction to Islamic finance : theory and practice - Iqbal, Zamir; Mirakhor, Abbas (Singapore : John Wiley & Sons (Asia), 2011)
The book explains the fundamental principles and functions of an economic, banking and financial system based on principles derived from the basic sources of Islam.
Includes glossary of Arabic terms.
Includes bibliographical references (p. 393-397) and index.
nif 26/04/13
Loans
Keywords: Finance; Finance; Financial institutions